Catalytic Enantioselective Functionalization of Unactivated Terminal Alkenes. Issue 8 (13th January 2016) - Coombs, John R.; Morken, James P.
Abstract: Terminal alkenes are readily available functional groups which appear in α‐olefins produced by the chemical industry, and they appear in the products of many contemporary synthetic reactions. While the organic transformations that apply to alkenes are amongst the most studied reactions in all of chemical synthesis, the number of reactions that apply to nonactivated terminal alkenes in a catalytic enantioselective fashion is small in number. This Minireview highlights the cases where stereocontrol in catalytic reactions of 1‐alkenes is high enough to be useful for asymmetric synthesis. Abstract : Growing the chain : Asymmetric synthesis using terminal alkenes as substrates enables hydrocarbon‐chain extension and concomitant functional‐group installation. Given the ready availability of terminal alkene substrates, their enantioselective transformation represents a powerful synthesis strategy. FG=functional group.